2014
DOI: 10.1016/j.devcel.2014.07.019
|View full text |Cite
|
Sign up to set email alerts
|

FLA8/KIF3B Phosphorylation Regulates Kinesin-II Interaction with IFT-B to Control IFT Entry and Turnaround

Abstract: The assembly and maintenance of cilia depends on intraflagellar transport (IFT). Activated IFT motor kinesin-II enters the cilium with loaded IFT particles comprising IFT-A and IFT-B complexes. At the ciliary tip, kinesin-II becomes inactivated, and IFT particles are released. Moreover, the rate of IFT entry is dynamically regulated during cilium assembly. However, the regulatory mechanism of IFT entry and loading/unloading of IFT particles remains elusive. We show that the kinesin-II motor subunit FLA8, a hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
145
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(150 citation statements)
references
References 50 publications
(68 reference statements)
4
145
1
Order By: Relevance
“…The distal segment may contain different proteins and often, a different microtubule structure (singlets). Lastly, the ciliary tip includes factors for IFT turnaround and microtubule dynamics [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The distal segment may contain different proteins and often, a different microtubule structure (singlets). Lastly, the ciliary tip includes factors for IFT turnaround and microtubule dynamics [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…They are returned from the ciliary tip to the base via cytoplasmic dynein 1b/2 (retrograde IFT) [69]. There are thus various points in the process of IFT where it might be regulated: IFT entry and exit of cilia, turnaround at the ciliary tip, anterograde and retrograde transport of IFT[1013]. …”
Section: Introductionmentioning
confidence: 99%
“…After reaching the tip, kinesin inactivation and dynein activation are a prerequisite for retrograde IFT. Interaction studies between IFT complex proteins and motors have so far not been very conclusive and, in some cases, contradictory (Baker et al 2003;Qin et al 2004;Follit et al 2009;Liang et al 2014). A direct interaction between heterotrimeric kinesin II and IFT20 was proposed for the mouse proteins based on a yeast two-hybrid assay (Baker et al 2003), but this could not be confirmed in an independent study (Follit et al 2009), and might have been a false positive interaction caused by coexpression of two coiled-coil proteins in the absence of their native binding partners.…”
Section: Association Between Ift Complexes and Ift Motorsmentioning
confidence: 99%